Method for recovering lithium, nickel-cobalt-manganese composite hydroxide and aluminum-copper powder from waste ternary lithium ion battery pole piece

By combining the pretreatment of waste ternary lithium-ion batteries with Fenton reaction combined with leaching process, the problem of excessive aluminum impurities and long process flow in the black powder in traditional recycling methods is solved, and the efficient recovery of lithium, nickel-cobalt-manganese composite hydroxides and high-purity aluminum-copper powder is achieved, reducing production costs.

CN119843060APending Publication Date: 2025-04-18HUNAN JIANGYE NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202510065248.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The traditional method of recycling waste ternary lithium-ion batteries has the problems of excessive aluminum impurities in black powder, not suitable for high-temperature pyrolysis, long process flow and high production and operation costs.

Method used

The factory waste cathode sheet was pretreated by a stripper and a cutting machine, and the Fenton reaction and ultrasonic assisted leaching process were carried out. The mixed iron salt solution of divalent iron salt and trivalent iron salt was used for the leaching reaction, which reduced the damage to the current collector metal, and high-purity aluminum powder and copper powder were obtained through hydrodynamic screening and specific gravity sorting.

Benefits of technology

It realizes efficient recycling of lithium, nickel, cobalt, manganese composite hydroxides and high-purity aluminum and copper powder, simplifies the process flow, reduces production costs, and improves recovery and product purity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843060A_ABST
    Figure CN119843060A_ABST
Patent Text Reader

Abstract

The invention discloses a method for recovering lithium, nickel cobalt manganese composite hydroxide and aluminum copper powder from a waste ternary lithium ion battery pole piece. The method comprises the following steps: treating waste pole pieces of a ternary plant or a mixture of positive and negative pole pieces by using a Fenton technology, leaching by using a mixed ferric salt solution, and filtering to obtain lithium-containing leachate and slag; adjusting the pH value of the leachate, oxidizing and filtering to obtain a purified solution and ferric hydroxide precipitate, and adding the purified solution and a lithium hydroxide solution into a reactor for coprecipitation to obtain a deeply purified solution and the nickel-cobalt-manganese composite hydroxide. And dissolving the ferric hydroxide precipitate with dilute acid, adding a reducing agent to generate a ferrous salt solution, and returning the ferrous salt solution for Fenton reaction and leaching reaction. And adding the sodium carbonate saturated solution into the deep purification solution, and crystallizing and precipitating to obtain the battery-grade lithium carbonate. And performing hydrodynamic screening on the leaching residues to obtain an aluminum-copper mixture and graphite residues, and performing grinding and specific gravity separation on the aluminum-copper mixture to obtain high-purity aluminum powder and copper powder. According to the method, the iron salt is directly leached from the pole piece, the used iron salt can be recycled, and the method is suitable for large-scale recovery of the waste ternary lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery recycling, and in particular to a method for recycling lithium, nickel-cobalt-manganese composite hydroxide and aluminum-copper powder from waste ternary lithium ion battery pole pieces. Background Art

[0002] With the emergence and development of new things such as power tools, electric vehicles and smart grids, the demand for lithium-ion batteries with high energy density, high power density and long cycle life has become more and more urgent. Nickel-cobalt-manganese ternary cathode materials are gradually becoming the mainstream products in the current cathode material market due to their higher energy density, lower cost and reliable safety performance, and have been widely used. However, compared with lithium iron phosphate materials, ternary cathode materials contain more valuable metals, such as lithium, nickel, and cobalt. The reserves of these precious metals in my country are limited. Therefore, the effective recovery and recycling of ternary cathode materials will not only help avoid environmental pollution, but also significantly reduce my country's external dependence on lithium, nickel and cobalt resources, thereby solving the problem of raw material sources for lithium power battery manufacturing.

[0003] In order to improve the range of pure electric vehicles, ternary lithium-ion power batteries are developing towards high-energy high-nickel cathode materials, including but not limited to 8-series and 9-series high-nickel cathode materials. Due to the high energy density of high-nickel cathode materials, the waste cathode sheets of such cathode materials are prone to sudden fire hazards when conventional crushing methods such as crushing and shredding are used. When the materials after crushing of waste high-nickel lithium-ion batteries are pyrolyzed at high temperature, when the pyrolysis temperature exceeds 400°C, thermal runaway generally occurs.

[0004] At present, the method of recycling used ternary lithium-ion batteries in the industry is usually to first use a crushing and sorting method to crush the used lithium-ion batteries to obtain black powder, copper powder and aluminum powder, and then use a hydrometallurgical process to leach the ternary black powder to recover lithium. However, there are some problems with the traditional crushing and sorting method. Specifically, this method uses multi-stage crushing, which leads to excessive crushing of the current collector aluminum foil and copper foil, resulting in too much aluminum and copper metal powder mixed into the black powder, especially aluminum powder. Because its specific gravity is close to that of black powder, when the specific gravity sorting method is used, the aluminum impurities in the sorted black powder will exceed the standard.

[0005] In the hydrometallurgical leaching process of ternary lithium-ion battery black powder, the acid leaching process is generally used. As shown in Chinese inventions CN 115627356A and CN 111261967A, sulfuric acid is often used as a strong acid. A large amount of sulfuric acid is consumed during the leaching process, and then sodium hydroxide is used to adjust the pH value. Both strong acids and strong bases are hazardous chemicals with strict requirements for storage and use, which not only increases the complexity of operation, but also increases the cost of wastewater treatment. In addition, strong acid leaching lacks selectivity, and all metal impurities in the black powder will dissolve into the leaching solution, especially the interference of aluminum impurities, resulting in a decrease in lithium recovery rate.

[0006] Secondly, for the valuable metals of nickel, cobalt and manganese in the ternary positive electrode materials, the traditional process in the industry adopts the extraction method, which uses strong acid to leach nickel, cobalt and manganese into the leachate, and then extracts manganese, cobalt and nickel separately in steps, and then strips them to obtain sulfates of nickel, cobalt and manganese, and then synthesizes nickel, cobalt and manganese composite hydroxide, that is, the ternary precursor. This synthesis process is long and the production and operation cost is high.

[0007] In summary, in the traditional recycling process of waste ternary lithium-ion batteries, the crushing and sorting process will cause excessive aluminum impurities in the black powder. High-nickel waste lithium-ion batteries are not suitable for high-temperature pyrolysis, and high-nickel positive electrode sheets cannot be crushed by conventional methods. Subsequent hydrometallurgy uses strong acids and alkalis, and the extraction of nickel, cobalt, and manganese metals needs to be extracted separately. The process is long and the production and operation costs are high. Summary of the invention

[0008] In view of the technical problems in the prior art such as the crushing and sorting process will cause excessive aluminum impurities in the black powder, high-nickel waste lithium-ion batteries are not suitable for high-temperature pyrolysis, and high-nickel positive electrodes cannot be crushed by conventional methods, the present invention proposes a method for recovering lithium, nickel-cobalt-manganese composite hydroxide and aluminum-copper powder from waste ternary lithium-ion battery electrodes. First, pre-treat the waste positive electrodes in the lithium-ion battery production process, use a slitting machine to slit the rolled waste electrodes to reduce the electrode width, and then cut the narrow rolled electrodes into short electrodes. For longer scattered electrodes, they are directly shortened; after the waste ternary lithium-ion batteries are crushed by tooth cutting, they are pre-treated in an environmentally friendly manner to obtain a mixture of sheet-like positive and negative electrodes. Then use Fe 2+ / H2O2 Fenton agent, with the assistance of ultrasound, treats the positive electrode sheet or the mixture of positive and negative electrode sheets, vibrates and strips the surface active materials of the electrode sheet, and then adds a mixed solution of divalent iron salt to directly leach the positive electrode sheet or the mixture of positive and negative electrode sheets. The divalent iron salt leaching process has good selectivity for ternary materials, only leaching lithium ions, but does not react with the current collector metal copper foil. The current collector aluminum foil will be passivated and basically insoluble in divalent iron salt. The leaching solution has few impurities, which simplifies the subsequent impurity removal cost and produces high purity lithium carbonate. When the positive electrode sheet is leached, battery-grade lithium carbonate and battery-grade nickel-cobalt-manganese composite hydroxide can be obtained; the positive and negative electrode fragments obtained by hydrodynamic screening of the leached solid phase slag are ground and gravity sorted to obtain high-purity aluminum powder and copper powder. The hydrometallurgical process involved in the present invention does not consume a large amount of strong acid and strong alkali; the leaching agent is simply regenerated and recycled for Fenton reaction and leaching reaction, which greatly reduces the cost of wastewater treatment.

[0009] In order to achieve the above-mentioned purpose of the present invention, a method for recovering lithium, nickel-cobalt-manganese composite hydroxide and aluminum-copper powder from waste ternary lithium-ion battery pole pieces specifically comprises the following steps:

[0010] S1. Pre-treating the waste positive electrode sheet of the ternary lithium-ion battery to obtain a regular sheet positive electrode sheet; or pre-treating the waste ternary lithium-ion battery to obtain a sheet positive and negative electrode mixture after removing the electrolyte, the diaphragm, and the shell;

[0011] S2. Add the regular sheet-shaped positive electrode sheet or the mixture of sheet-shaped positive and negative electrode sheets obtained in step S1 to a divalent iron salt solution, and then add hydrogen peroxide to perform a Fenton reaction under the assistance of ultrasound;

[0012] S3. A mixed iron salt solution is prepared by using a trivalent iron salt and a divalent iron salt, and then added to the mixture obtained after the Fenton reaction in step S2 for leaching reaction, and filtered to separate the leachate containing lithium and iron ions and the solid slag, wherein the solid slag is a solid slag including only aluminum fragments or a solid slag including a mixture of aluminum and copper fragments;

[0013] S4. The lithium hydroxide solution is added to the lithium-containing, iron ion leachate obtained in step S3, the pH value of the solution is adjusted, and then air or oxygen is introduced to produce iron hydroxide precipitation, and the purified lithium-containing solution and iron hydroxide solid phase are obtained by filtration;

[0014] S5. The lithium hydroxide solution and the purified lithium-containing solution obtained in step S4 are added to a reactor under a nitrogen atmosphere, and the pH value is further adjusted to produce a nickel-cobalt-manganese hydroxide precipitate, which is filtered and separated to obtain a deeply purified lithium-containing solution and a nickel-cobalt-manganese composite hydroxide;

[0015] S6. adding a saturated sodium carbonate solution to the deeply purified lithium-containing solution obtained in step S5, filtering to obtain lithium carbonate and a crystallization mother liquor, evaporating and concentrating the crystallization mother liquor, and using the concentrated mother liquor to prepare the lithium hydroxide solution of step S4 or / and step S5;

[0016] S7. adding dilute acid to the ferric hydroxide solid phase obtained in step S4, stirring the reaction to obtain a trivalent iron salt solution, returning part of the trivalent iron salt solution to step S3 for preparing a mixed iron salt solution, adding a reducing agent to the remaining part for reduction reaction to obtain a divalent iron salt solution, returning part (usually only a small part) of the divalent iron salt solution to step S2 for preparing a Fenton reagent, and returning the remaining part (usually most of it) to step S3 for preparing a mixed iron salt solution;

[0017] S8. The solid phase slag including only aluminum fragments or the solid phase slag including a mixture of aluminum and copper fragments obtained after leaching in step S3 is washed with the crystallization mother liquor obtained in step S6, and then washed with hot water;

[0018] S9. The solid phase slag including only aluminum fragments after washing is crushed by teeth cutting in a wet state, and then hydrodynamic screening is used to separate the broken aluminum flakes and carbon slag; the solid phase slag including a mixture of aluminum and copper fragments after washing is separated by hydrodynamic screening to obtain a mixture of aluminum and copper fragments and graphite slag;

[0019] S10. After drying and grinding the mixture of aluminum and copper fragments, separate them using a specific gravity separator to obtain high-purity aluminum powder and copper powder.

[0020] Furthermore, in step S1, the pretreatment of the factory waste positive electrode sheets is to use a slitting machine in the lithium-ion battery production workshop to slit the rolled electrode sheets into rolled electrode sheets with a width less than 100 mm, and then use a electrode sheet cutting machine to cut the rolled electrode sheets into electrode sheets with a length less than 100 mm; for scattered electrode sheets with a length and width exceeding 100 mm, they are cut to a length and width less than 100 mm.

[0021] Furthermore, in step S1, the pretreatment of the waste ternary lithium-ion batteries is to perform a tooth cutting and crushing on the waste ternary lithium-ion batteries under a nitrogen atmosphere, and then perform low-temperature pyrolysis (preferably 300-400°C, more preferably 350-380°C) at a temperature not exceeding 400°C to completely volatilize and carbonize the electrolyte and the diaphragm, and then remove the shell and the pile head through air separation to obtain a mixture of positive and negative electrode sheets. The exhaust gas generated by the pyrolysis is subjected to secondary combustion and environmental protection treatment before being discharged in compliance with emission standards.

[0022] Furthermore, in step S1, the positive electrode materials of the factory waste positive electrode sheets or waste ternary lithium-ion batteries are all high-nickel ternary positive electrode materials, preferably 8 series and 9 series high-nickel positive electrode materials.

[0023] The above-mentioned single tooth cutting crushing is a single shearing crushing, and the pole pieces are in regular flakes. Single shearing can greatly reduce the content of fine metal powder in the material relative to multi-stage crushing or fine grinding; through shearing crushing, the size of waste ternary lithium-ion battery fragments can be controlled within 10 to 45 mm.

[0024] Further, in step S2, in the Fenton reaction, the molar ratio of the divalent iron salt to the hydrogen peroxide is (0.3-3):1; the pH value of the solution is 2.5-4.0, preferably 2.8-3.5; the mass fraction of the hydrogen peroxide is 1-10%; the liquid-solid mass ratio is (1-10):1; the reaction time is 30-90 minutes; and the ultrasonic power intensity is 50-200 W / cm 2 ; The divalent iron salt is selected from one of ferrous sulfate, ferrous nitrate and ferrous bromide.

[0025] The Fenton reaction is the reaction of H2O2 and Fe 2+ The direct electron transfer between them leads to the generation of HO· free radicals, while Fe 2+ Oxidized to Fe 3+ .

[0026] Fe 2+ +H2O2→Fe 3+ +HO+OH

[0027] HO free radicals can produce strong oxidation and decomposition effects on PVDF binder in positive electrode materials and CMC / SBR binder in negative electrode materials, reduce the adhesion between active materials and current collector aluminum foil and copper foil, and improve the stripping efficiency of active materials from the current collector surface; the strong cavitation effect of ultrasonic waves on the pole powder on the pole piece surface plays a synergistic role in the dispersion and stripping of pole powder.

[0028] Furthermore, in step S3, the divalent iron salt is selected from one of ferrous sulfate, ferrous nitrate, and ferrous bromide, and in the mixed iron salt solution, the molar amount of the trivalent iron salt is 40 to 90% of the molar amount of the divalent iron salt; the molar ratio of the divalent iron salt to the active material in the positive electrode sheet is (0.5 to 1.0):1, and the molar ratio of the trivalent iron salt to the active material in the positive electrode sheet is (0.3 to 0.8):1.

[0029] Furthermore, in step S3, the liquid-solid mass ratio of the mixed iron salt solution to the electrode material is (10-30):1, preferably (20-25):1; the temperature of the leaching reaction is 40-95°C, and the time is 60-90 minutes.

[0030] The reaction equation of the leaching process in step S3 is shown in the following reaction equation (taking 811 type positive electrode material as an example):

[0031] 3LiNi 0.8 Co 0.1 Mn0.1 O2+3Fe 2+ +Fe 3+ +6H2O=3Li + +4Fe(OH)3+2.4Ni 2+ +0.3Co 2+ +0.3Mn 2+ .

[0032] Furthermore, in step S4, the pH value is adjusted to 3.5-5.0; air or oxygen is blown in to oxidize all the iron ions in the leaching solution to trivalent iron ions.

[0033] Furthermore, in step S5, the concentration of the lithium hydroxide solution is 1 to 10 mol / L, and the pH value is adjusted to 8 to 10; the nickel-cobalt-manganese composite hydroxide obtained in S5 can be used for the preparation of a ternary precursor, specifically: the nickel-cobalt-manganese composite hydroxide is added with a dilute acid for dissolution to obtain a nickel-cobalt-manganese salt mixed solution, and under a nitrogen atmosphere, the nickel-cobalt-manganese salt mixed solution is flowed to a reactor together with a sodium hydroxide solution and an ammonia solution for precipitation reaction to prepare a ternary precursor.

[0034] Furthermore, in step S6, when the leaching raw material is factory waste positive electrode sheets, the obtained lithium carbonate is battery-grade lithium carbonate.

[0035] Furthermore, in step S7, the concentration of the dilute acid is 0.05-2 mol / L, and the dilute acid is one of sulfuric acid, nitric acid, and bromic acid; the trivalent iron salt solution obtained by adding the dilute acid is returned to step S3, and the proportion of the trivalent iron salt used to prepare the divalent iron salt solution is 30-40%.

[0036] Furthermore, in step S7, the temperature of the reduction reaction is 50-80°C, and the reduction reaction is stopped when the trivalent iron salt is completely reduced and converted into divalent iron salt, and the time is usually 30-60 minutes. The reducing agent is selected from one of sulfur dioxide, iron powder, and ethanol, preferably sulfur dioxide; the divalent iron salt solution obtained by reduction is returned to the divalent iron salt ratio for preparing Fenton reagent in step S2 in a range of 2-10%.

[0037] The reaction formula for sulfur dioxide reducing trivalent iron salt is as follows (taking sulfur dioxide as a reducing agent as an example):

[0038] 2Fe 3+ +SO2+2H2O=2Fe 2+ +SO4 2- +4H +

[0039] Furthermore, in step S8, the crystallization mother liquor washing liquid and the hot water washing liquid can be recycled, and the crystallization mother liquor is returned to step S4 and step S5 to prepare the lithium hydroxide solution; the hot water washing liquid is returned to step S7 to prepare the dilute acid.

[0040] Furthermore, the tooth cutting and crushing in step S9 is a one-time shearing and crushing, which is similar to the tooth cutting and crushing of the waste ternary lithium-ion batteries in step S1, but the shearing needs to be performed in a wet state.

[0041] Hydrodynamic screening is a centrifugal separation using water as the medium. There is no filter cloth on the surface of the screen inside the centrifuge. The screen aperture is 3 to 8 mm, and the hole spacing is between 2 and 5 mm. The mixture of metal collector and solid slag is made into wet slurry with water and then pumped into the centrifuge without filter cloth. When factory waste positive electrode sheets are used as raw materials, aluminum fragments and carbon slag are separated through the screen holes. When waste lithium-ion batteries are used as raw materials, aluminum and copper fragment mixtures and graphite slag are separated through the screen holes.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] (1) The pole powder is peeled off by combining Fenton reaction and ultrasound. The free radicals produced by Fenton reaction have very strong oxidizing ability. In acidic medium, the redox potential reaches 2.7V, which can produce strong oxidation and decomposition effects on PVDF binder in positive electrode active materials of lithium-ion batteries and CMC / SBR binder in negative electrode active materials, reducing the adhesion of pole powder. Under the synergy of strong cavitation effect of ultrasound, the pole powder on the metal surface of the current collector is separated from aluminum and copper foil. There is no need to use high-energy operation method of high-temperature pyrolysis and carbonization of adhesives and then dry peeling, which greatly reduces the operating energy consumption.

[0044] (2) The present invention does not adopt the method of first crushing and dry stripping, sorting out the black powder, and then entering the hydrometallurgical process. Instead, it directly enters the leaching process from the electrode, shortening the process flow. On the one hand, it greatly reduces the production line investment and production costs. On the other hand, it eliminates the inevitable dust overflow during the dry stripping of the electrode, thereby improving the black powder recovery rate.

[0045] (3) The present invention uses a non-acidic mixed iron salt solution of divalent iron and trivalent iron for leaching reaction, and does not use strong acids or strong bases. The process and storage and transportation are safe and environmentally friendly, and the iron salt solution can be recycled and reused, reducing the subsequent wastewater treatment costs.

[0046] (4) The non-acid leaching process has significantly better selectivity. Metal impurities such as aluminum and copper are basically not dissolved in the solution, which reduces the cost of subsequent impurity removal, and the purity of the lithium-containing leaching solution is high. Non-acid leaching of positive electrode sheets can obtain battery-grade lithium carbonate and nickel-cobalt-manganese composite hydroxide that can be used to prepare ternary precursors. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0048] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments, but the present invention is not limited thereto.

[0049] Example 1

[0050] The raw material of this embodiment is the factory waste positive electrode sheet of ternary high nickel (811) lithium ion battery. 1.15 kg of factory waste positive electrode sheet of ternary high nickel lithium ion battery is weighed and added to the leaching tank. 10 liters of pure water are added and then 47 grams of ferrous sulfate heptahydrate are added. The pH value of the solution is adjusted to 3.0. Stirring and ultrasonic wave are started first. The ultrasonic wave intensity is 100 W / cm 2 , slowly add 114 ml of 10% hydrogen peroxide, and perform Fenton reaction for 60 minutes. Then weigh 2.29 kg of ferrous sulfate heptahydrate and 1.92 kg of ferric sulfate, and prepare 20 liters of mixed iron salt solution with pure water. The concentration of trivalent iron ions in the mixed iron salt solution is 58% of the concentration of divalent iron ions. Add the mixed iron salt solution to the reaction mixture after the Fenton reaction, heat to 90 ° C, stir and leaching for 40 minutes, filter the leachate and solid phase residue, and wash the leach residue. Detect the metal content in the leachate and leach residue. The leaching rates of lithium, nickel, cobalt, and manganese are calculated to be 99.56%, 98.67%, 98.34%, and 98.73%, respectively.

[0051] Slowly add a 3 mol / L lithium hydroxide solution to the leachate, adjust the pH value to 4.5, then introduce air for 60 minutes, and filter to obtain the purified leachate and iron hydroxide precipitate. Under a nitrogen atmosphere, slowly add a 3 mol / L lithium hydroxide solution and the purified leachate to the reactor, adjust the pH value to 10, and filter to obtain a deeply purified leachate and a nickel-cobalt-manganese composite hydroxide precipitate. Heat the deeply purified leachate to 90°C, add a saturated sodium carbonate solution to react for 1 hour, filter and wash with hot water to obtain lithium carbonate and mother liquor, the purity of lithium carbonate is calculated to be 99.6%, and the comprehensive recovery rate is 94.6%. After evaporation and concentration, the mother liquor is returned to adjust the pH value of the purified solution.

[0052] Slowly add 0.1 mol / L dilute sulfuric acid to the ferric hydroxide precipitate, stop when the solution pH is 1, and react to obtain a ferric sulfate solution. Reserve 36% of the ferric sulfate solution, and slowly introduce sulfur dioxide into the remaining solution for reduction reaction. The temperature is 55°C and the reaction is stirred for 1 hour to obtain a ferrous sulfate solution, wherein 3% of the ferrous sulfate solution is used to return to the Fenton reaction process to prepare the Fenton reagent, and the remaining 97% of the ferrous sulfate solution and the reserved ferric sulfate solution are returned to the leaching process for leaching reaction.

[0053] 0.2 mol / L of dilute sulfuric acid was added to the nickel-cobalt-manganese composite hydroxide precipitate obtained above to prepare a nickel-cobalt-manganese sulfate solution, which was co-precipitated with a sodium hydroxide solution and aqueous ammonia in a nitrogen atmosphere to obtain a nickel-cobalt-manganese precursor.

[0054] The leached residue obtained above was sheared and crushed, and after being prepared into slurry, aluminum flakes and carbon slag were separated by a hydraulic screening device, and the purity of the aluminum flakes was 99.5%.

[0055] Example 2

[0056] The raw material of this example is ternary 8 series (811) high nickel lithium ion battery. The waste lithium ion battery is first crushed by tooth cutting in a nitrogen atmosphere, and pyrolyzed at low temperature, with the pyrolysis temperature at 370°C, to obtain a mixture of positive and negative electrode sheets. Weigh 1.47 kg of the electrode sheet mixture, add it to the leaching tank, add 10 liters of pure water, and then add 47 grams of ferrous sulfate heptahydrate, adjust the solution pH to 3.0, start stirring and ultrasonic wave, and the ultrasonic wave intensity is 100 W / cm 2 , slowly add 120 ml of 10% hydrogen peroxide, and perform Fenton reaction for 60 minutes. Then weigh 2.29 kg of ferrous sulfate heptahydrate and 1.92 kg of ferric sulfate, and prepare 20 liters of mixed iron salt solution with pure water. The concentration of trivalent iron ions in the mixed iron salt solution is 58% of the concentration of divalent iron ions. Add the mixed iron salt solution to the reaction mixture after the Fenton reaction, heat to 90 ° C, stir and leaching for 40 minutes, filter the leachate and solid phase residue, and wash the leach residue. Detect the metal content in the leachate and leach residue. The leaching rates of lithium, nickel, cobalt, and manganese are calculated to be 99.26%, 98.43%, 98.10%, and 98.35%, respectively.

[0057] Slowly add a 3 mol / L lithium hydroxide solution to the leachate, adjust the pH value to 4.5, then introduce air for 60 minutes, and filter to obtain the purified leachate and iron hydroxide precipitate. Under a nitrogen atmosphere, slowly add a 3 mol / L lithium hydroxide solution and the purified leachate to the reactor, adjust the pH value to 10, filter, and obtain a deeply purified leachate and a nickel-cobalt-manganese composite hydroxide precipitate. Heat the deeply purified leachate to 90°C, add a saturated sodium carbonate solution to react for 1 hour, filter, and wash with hot water to obtain lithium carbonate and mother liquor. The purity of lithium carbonate is detected to be 99.3%, and the comprehensive recovery rate is 93.8%. After evaporation and concentration, the mother liquor is returned to adjust the pH value of the purified solution.

[0058] Use dilute sulfuric acid with a concentration of 0.1 mol / L to slowly add ferric hydroxide precipitate, and stop when the pH of the solution is 1. The reaction obtains a ferric sulfate solution, and 35% of the ferric sulfate solution is reserved. The remaining solution is slowly introduced with sulfur dioxide for reduction reaction. The temperature is 55°C and the reaction is stirred for 1 hour to obtain a ferrous sulfate solution, wherein 3% of the ferrous sulfate solution is used to return to the Fenton reaction process to prepare the Fenton reagent, and the remaining 97% of the ferrous sulfate solution and the reserved ferric sulfate solution are returned to the leaching process for leaching reaction.

[0059] The leached residue obtained above is added with water to form a slurry, and the aluminum-copper fragment mixture and graphite residue are separated by a hydrodynamic screening device. The aluminum-copper fragment mixture is dried, ground, and then separated by specific gravity to obtain aluminum powder and copper powder, with the purity of aluminum powder being 99.1% and the purity of copper powder being 99.4%.

Claims

1. A method for recovering lithium, nickel-cobalt-manganese composite hydroxide and aluminum-copper powder from waste ternary lithium-ion battery pole pieces, characterized in that: The following steps are involved: S1. Pre-treating the waste positive electrode sheet of the ternary lithium-ion battery to obtain a regular sheet positive electrode sheet; or pre-treating the waste ternary lithium-ion battery to obtain a sheet positive and negative electrode mixture after removing the electrolyte, the diaphragm, and the shell; S2. Add the regular sheet-shaped positive electrode sheet or the mixture of sheet-shaped positive and negative electrode sheets obtained in step S1 to a divalent iron salt solution, and then add hydrogen peroxide to perform a Fenton reaction under the assistance of ultrasound; S3. A mixed iron salt solution is prepared by using a trivalent iron salt and a divalent iron salt, and then added to the mixture obtained after the Fenton reaction in step S2 for leaching reaction, and filtered to separate the leachate containing lithium and iron ions and a solid phase slag, wherein the solid phase slag is a solid phase slag including only aluminum fragments or a solid phase slag including a mixture of aluminum and copper fragments; S4. The lithium hydroxide solution is added to the lithium-containing, iron ion leachate obtained in step S3, the pH value of the solution is adjusted, and then air or oxygen is introduced to produce iron hydroxide precipitation, and the purified lithium-containing solution and iron hydroxide solid phase are obtained by filtration; S5. The lithium hydroxide solution and the purified lithium-containing solution obtained in step S4 are added to a reactor under a nitrogen atmosphere, and the pH value is further adjusted to produce a nickel-cobalt-manganese hydroxide precipitate, which is filtered and separated to obtain a deeply purified lithium-containing solution and a nickel-cobalt-manganese composite hydroxide; S6. adding a saturated sodium carbonate solution to the deeply purified lithium-containing solution obtained in step S5, filtering to obtain lithium carbonate and a crystallization mother liquor, evaporating and concentrating the crystallization mother liquor, and using the concentrated mother liquor to prepare the lithium hydroxide solution of step S4 or / and step S5; S7. adding dilute acid to the ferric hydroxide solid phase obtained in step S4, stirring the reaction to obtain a trivalent iron salt solution, returning part of the trivalent iron salt solution to step S3 for preparing a mixed iron salt solution, adding a reducing agent to the remaining part for reduction reaction to obtain a divalent iron salt solution, returning part of the divalent iron salt solution to step S2 for preparing a Fenton reagent, and returning the remaining part to step S3 for preparing a mixed iron salt solution; S8. The solid phase slag including only aluminum fragments or the solid phase slag including a mixture of aluminum and copper fragments obtained after leaching in step S3 is washed with the crystallization mother liquor obtained in step S6, and then washed with hot water; S9. The solid phase slag including only aluminum fragments after washing is crushed by teeth cutting in a wet state, and then hydrodynamic screening is used to separate the broken aluminum flakes and carbon slag; the solid phase slag including a mixture of aluminum and copper fragments after washing is separated by hydrodynamic screening to obtain a mixture of aluminum and copper fragments and graphite slag; S10. After drying and grinding the mixture of aluminum and copper fragments, separate them using a specific gravity separator to obtain high-purity aluminum powder and copper powder.

2. The method for recovering lithium, nickel-cobalt-manganese composite hydroxide and aluminum-copper powder from waste ternary lithium-ion battery pole pieces according to claim 1, characterized in that: In step S1, the pretreatment of the factory waste positive electrode sheets is to use the slitting machine of the lithium-ion battery production workshop to slit the rolled electrode sheets into rolled electrode sheets with a width of less than 100 mm, and then use the electrode sheet cutting machine to cut the rolled electrode sheets into electrode sheets with a length of less than 100 mm. For scattered electrode sheets with a length and width exceeding 100 mm, they are cut to a length and width of less than 100 mm; the pretreatment of the waste ternary lithium-ion batteries is to perform a tooth cutting and crushing on the waste ternary lithium-ion batteries in a nitrogen atmosphere, and then perform low-temperature pyrolysis at a temperature not exceeding 400°C to completely volatilize and carbonize the electrolyte and the diaphragm, and then remove the shell and the pile head through air separation to obtain a mixture of positive and negative electrode sheets. The tail gas generated by the pyrolysis is subjected to secondary combustion environmental protection treatment and meets the emission standards.

3. The method for recovering lithium, nickel-cobalt-manganese composite hydroxide and aluminum-copper powder from waste ternary lithium-ion battery pole pieces according to claim 1, characterized in that: In step S2, in the Fenton reaction, the molar ratio of the divalent iron salt to the hydrogen peroxide is (0.3-3):1; the pH value of the solution is 2.5-4.0, preferably 2.8-3.5; the mass fraction of the hydrogen peroxide is 1-10%; the liquid-solid mass ratio is (1-10):1; the reaction time is 30-90 minutes; and the ultrasonic power intensity is 50-200 W / cm 2 ; The divalent iron salt is selected from one of ferrous sulfate, ferrous nitrate and ferrous bromide.

4. The method for recovering lithium, nickel-cobalt-manganese composite hydroxide and aluminum-copper powder from waste ternary lithium-ion battery pole pieces according to claim 1, characterized in that: In step S3, the divalent iron salt is selected from one of ferrous sulfate, ferrous nitrate, and ferrous bromide. In the mixed iron salt solution, the molar amount of the trivalent iron salt is 40 to 90% of the molar amount of the divalent iron salt; the molar ratio of the divalent iron salt to the active material in the positive electrode sheet is (0.5 to 1.0):1, and the molar ratio of the trivalent iron salt to the active material in the positive electrode sheet is (0.3 to 0.8):

1.

5. The method for recovering lithium, nickel-cobalt-manganese composite hydroxide and aluminum-copper powder from waste ternary lithium-ion battery pole pieces according to claim 1, characterized in that: In step S3, the liquid-solid mass ratio of the mixed iron salt solution to the electrode material is (10-30):1, preferably (20-25):1; the leaching reaction temperature is 40-95°C, and the time is 60-90 minutes.

6. The method for recovering lithium, nickel-cobalt-manganese composite hydroxide and aluminum-copper powder from waste ternary lithium-ion battery pole pieces according to claim 1, characterized in that: In step S4, the pH value is adjusted to 3.5-5.0; air or oxygen is blown in to oxidize all the iron ions in the leaching solution to trivalent iron ions.

7. The method for recovering lithium, nickel-cobalt-manganese composite hydroxide and aluminum-copper powder from waste ternary lithium-ion battery pole pieces according to claim 1, characterized in that: In step S5, the concentration of the lithium hydroxide solution is 1-10 mol / L, and the pH value is adjusted to 8-10; in step S6, when the leaching raw material is factory waste positive electrode sheets, the obtained lithium carbonate is battery-grade lithium carbonate.

8. The method for recovering lithium, nickel-cobalt-manganese composite hydroxide and aluminum-copper powder from waste ternary lithium-ion battery pole pieces according to claim 1, characterized in that: In step S7, the concentration of the dilute acid is 0.05-2 mol / L, and the dilute acid is one of sulfuric acid, nitric acid, and bromic acid; the ferric salt solution obtained by adding the dilute acid is returned to step S3 for preparing the ferric salt solution, and the proportion of the ferric salt is 30-40%; the temperature of the reduction reaction is 50-80°C, and the reduction reaction is stopped when the ferric salt is completely reduced and converted into ferrous salt, and the time is 30-60 minutes, and the reducing agent is selected from one of sulfur dioxide, iron powder, and ethanol, preferably sulfur dioxide; the ferrous salt solution obtained by reduction is returned to step S2 for preparing the Fenton agent, and the proportion of the ferric salt is 2-10%.

9. The method for recovering lithium, nickel-cobalt-manganese composite hydroxide and aluminum-copper powder from waste ternary lithium-ion battery pole pieces according to claim 1, characterized in that: In step S8, the crystallization mother liquor washing liquid and the hot water washing liquid can be recycled, and the crystallization mother liquor is returned to step S4 or / and step S5 to prepare the lithium hydroxide solution; The hot water washing liquid is returned to step S7 for preparing the dilute acid.

10. The method for recovering lithium, nickel-cobalt-manganese composite hydroxide and aluminum-copper powder from waste ternary lithium-ion battery pole pieces according to any one of claims 1 to 9, characterized in that: In step S1, the positive electrode materials of the waste positive electrode sheets or waste ternary lithium-ion batteries are all high-nickel ternary positive electrode materials, preferably 8 series and 9 series high-nickel positive electrode materials.

Citation Information

Patent Citations

  • Recovery method of waste lithium batteries and battery-grade nickel-cobalt-manganese mixed crystal recovered and prepared by adopting method

    CN111261967A

  • Waste ternary lithium battery metal recovery method

    CN115627356A

  • Recovery method of waste lithium battery

    CN107317064A

  • Recycle method for cathode material of nickel-cobalt-manganese acid lithium battery

    CN111206153A

  • Recycling method for extracting lithium, copper and aluminum from waste lithium iron phosphate battery

    CN119220819A

Cited By

  • Method for treating electrolyte after wet crushing of waste lithium ion battery

    CN120453548A

  • Strong-covalence manganese oxide-based Fenton-like catalyst based on waste high-manganese ternary lithium battery recycling as well as preparation method and application of strong-covalence manganese oxide-based Fenton-like catalyst

    CN120999006A

  • Waste lithium ion battery recycling method based on manganese redox cycle

    CN121416662A

  • A method for recycling waste lithium ion batteries based on manganese redox cycle

    CN121416662B